2002
DOI: 10.1016/s0022-2860(02)00147-3
|View full text |Cite
|
Sign up to set email alerts
|

Torsional potential energy surfaces and vibrational levels in trans Stilbene

Abstract: Quantum chemical calculations of vibrational frequencies of Stilbene were followed by the computation of the potential energy surface for the two rotors related to the single bonds. By the flexible model approach applied to the computed surface we have confirmed previous assignment of mode 37 and determined frequency of the elusive mode 48. The same analysis was performed not only for the ground, but also for the excited electronic state. The shape of the potential energy surface in S 0 is in agreement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…[69][70][71] To be able to simulate the Franck-Condon spectra, we set the corresponding frequencies to be real-valued, small positive numbers taken from experiment ͑compare Table II͒ as will be outlined in detail below. Imaginary frequencies were obtained from both the TDDFT and the CASSCF treatment of the S 1 state for mode 37 ͑A u ͒ representing the ethylenic torsion.…”
Section: B High-resolution S 0 \ S 1 Absorption and S 0 ] S 1 Fluorementioning
confidence: 99%
See 1 more Smart Citation
“…[69][70][71] To be able to simulate the Franck-Condon spectra, we set the corresponding frequencies to be real-valued, small positive numbers taken from experiment ͑compare Table II͒ as will be outlined in detail below. Imaginary frequencies were obtained from both the TDDFT and the CASSCF treatment of the S 1 state for mode 37 ͑A u ͒ representing the ethylenic torsion.…”
Section: B High-resolution S 0 \ S 1 Absorption and S 0 ] S 1 Fluorementioning
confidence: 99%
“…Based on both experiment 56 and theory 69 it has been emphasized that the pronounced anharmonicity of this torsional potential is indispensable for understanding the vibrational level spacing and the intensities of the Franck-Condon progressions of mode 37. 4͑a͔͒, indeed, exhibits pronounced features at 83 cm −1 and a weaker line at 95 cm −1 even though the calculated intensities of both lines are still somewhat too low as compared to the experimental results.…”
Section: ͑42͒mentioning
confidence: 99%
“…In addition, our gasphase calculations for an isolated DEST cation (Supplementary Figure S13) estimate a barrier of 0.052 eV for the rotation of the acceptor moiety as it moves out of the molecular plane for TICT-state formation. Using a simple Arrhenius model with an approximated low-frequency torsional mode of ∼50−60 cm −1 (C−C bond rotation) 42,43 for the pre-exponential factor, we obtained a rate of ∼2 × 10 11 s −1 for excited relaxation to the TICT minimum. The calculated rate suggests a rise time of ∼1−5 ps, which is slightly longer than the experimentally observed rise times in methanol or water by TA.…”
mentioning
confidence: 99%
“…Since the large dimensions of the systems prevent the use of the most sophisticated post-Hartree-Fock models, several semi-empirical or perturbative methods were used in conjunction with approaches rooted into the density functional theory (DFT) to get an adequate picture of conjugation length effects in these systems. 12 DFT and timedependent (TD)-DFT at the B3LYP/6-31G(d) and 6-311++G(d,p) levels of theory were employed to determine the Raman, infrared (IR) and fluorescence excitation spectra in the S1 state 13 with the help of empirical scaling factors. For instance, computations at the configuration interaction (CI) level indicated that TSB adopts a cis conformation in the excited state 7 , whereas the molecule could be non-planar in its ground electronic state.…”
Section: Introductionmentioning
confidence: 99%